STRATEGI UMKM TAX CENTER UNIVERSITAS GUNADARMA MENEMBUS PASAR GLOBAL (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
Gunadarma University (UG) is consistently actively developing Micro Small and Medium Enterprises (MSMEs), especially in the Depok City area. Gunadarma University, through the tax centre, continues to collaborate with industry players and several related parties to support government programs in empowering and advancing MSMEs, where one of the activities carried out is assistance services for MSME needs. Assistance services for MSME need to be carried out by the PKM Tax Center team at Gunadarma University. PKM activities take the form of assisting MSMEs through digital marketing platforms, product photos and legal aspects as a strategic effort for MSMEs to penetrate the global market. This PKM activity aims to improve the capabilities of MSME managers and owners in using digital platforms and product photos as sales machines for MSMEs and understanding the legal aspects needed to penetrate the global market. The method of service activities is education and mentoring through consultation and discussion. This activity was attended by 40 MSMEs assisted by the Gunadarma University Tax Center and PKM-Abdimas Lecturers. The result of this service activity is that MSMEs assisted by the Gunadarma University Tax Center can understand and increase their insight into digital marketing materials, become familiar with product photos using AI and understand what legal aspects must be met to penetrate the global market through education. Accompanying lecturers as implementers of community service can help MSMEs answer the problems they face through consultation and discussion corners.  ---   Universitas Gunadarma (UG) konsistensi aktif melakukan pembinaan Usaha Mikro, Kecil dan Menengah (UMKM), khususnya di wilayah Kota Depok. Universitas Gunadarma melalui tax center terus berkolaborasi dengan para pelaku industri dan beberapa pihak terkait untuk mendukung program pemerintah dalam pemberdayaan dan memajukan UMKM, dimana salah satu kegiatan yang dilakukan adalah layanan pendampingan kebutuhan UMKM. Layanan pendampingan kebutuhan UMKM yang dilakukan oleh tim PKM Tax Center Universitas Gunadarma. Kegiatan PKM berupa pendampingan UMKM melalui platform pemasaran digital, foto produk dan aspek legalitas sebagai upaya strategi UMKM menembus pasar global. Tujuan kegiatan PKM  ini untuk meningkatkan kapabilitas pengelola dan pemilik UMKM dalam pemanfaatan platform digital, foto produk sebagai mesin penjualan bagi UMKM serta memahami aspek legalitas yang diperlukan untuk menembus pasar global.  Metode kegiatan pengabdian ini ceramah, pendampingan melalui konsultasi dan diskusi. Kegiatan ini diikuti oleh 40 pelaku UMKM binaan Tax Center Universitas Gunadarma dan Dosen PKM-Abdimas. Hasil kegiatan pengabdian ini adalah UMKM binaan Tax Center Universitas Gunadarma mampu memahami dan menambah wawasan mengenai materi pemasaran digital, mengenal foto produk dengan AI dan paham aspek legalitas apa saja yang harus dipenuhi untuk menembus pasar global melalui ceramah. Dosen pendamping sebagai pelaksana pengabdian masyarakat dapat membantu UMKM menjawab permasalahan yang dihadapi dengan  melalui pojok konsultasi dan diskusi.
Keywords: Digital marketing; product photos; legal aspects